Pendampingan Perguruan Tinggi dalam Rangka Peningkatan Profesi dan Karir Dosen Sesuai dengan Kebijakan Mendiktisainteks 2025 - Effendi, Mohammad Sofwan; Mayasari, Linda Ika; Soraya, Evitha; Wibowo, Agus; Suparno; Suratno, Ujang; Faqih, Achmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The national policy stipulated in the Regulation of the Minister of Education, Culture, Research, and Technology Number 44 of 2024 on the Profession, Career, and Income of Lecturers, although its implementation has been postponed through the Decree of the Minister of Higher Education, Science, and Technology Number 63/M/2025, requires higher education institutions to enhance the governance of lecturers’ career management in a more accountable, transparent, and performance-based manner. Universitas Wiralodra Indramayu and Universitas Swadaya Gunung Jati Cirebon, as partner private universities in this Community Service Program, still face challenges related to the alignment of internal regulations, operational procedures, and human resource capacity in managing lecturers’ careers. This program aimed to strengthen institutional readiness and improve the understanding of lecturers and academic administrators through institutional mentoring. The methods employed included situation analysis, problem mapping, development of Standard Operating Procedures (SOPs) for lecturers’ professional and career services, socialization activities, focus group discussions (FGDs), and implementation assistance. The initial survey results indicated that only approximately 18–30% of lecturers had a good understanding of career-related regulations and mechanisms prior to the program. Following the mentoring activities, an improvement in understanding was observed, as reflected in a higher proportion of lecturers who comprehended functional rank promotion mechanisms, performance assessment based on the tridharma of higher education, and career service procedures in accordance with the established SOPs. In addition to enhancing human resource understanding, this program produced an agreed and implementable SOP for lecturers’ career services and increased the institutional readiness of the partner universities to respond to national policy implementation. Abstrak Kebijakan Kebijakan nasional melalui Permendikbudristek Nomor 44 Tahun 2024 tentang Profesi, Karir, dan Penghasilan Dosen, meskipun penetapannya ditunda melalui Keputusan Mendiktisainteks Nomor 63/M/2025, menuntut perguruan tinggi untuk meningkatkan kesiapan tata kelola karir dosen yang lebih akuntabel, transparan, dan berbasis kinerja. Universitas Wiralodra Indramayu dan Universitas Swadaya Gunung Jati Cirebon sebagai perguruan tinggi swasta mitra dalam kegiatan Pengabdian kepada Masyarakat (PkM) masih menghadapi kendala dalam penyelarasan regulasi internal, prosedur operasional, serta kapasitas sumber daya manusia dalam pengelolaan karir dosen. Kegiatan PkM ini bertujuan untuk memperkuat kesiapan kelembagaan dan meningkatkan pemahaman dosen serta pengelola melalui pendampingan institusional yang sistematis. Metode yang digunakan meliputi analisis situasi, penyusunan peta masalah, perumusan Prosedur Operasional Standar (POS) layanan profesi dan karir dosen, sosialisasi, Focus Group Discussion (FGD), serta pendampingan implementasi. Hasil survei awal menunjukkan bahwa hanya sekitar 18–30% dosen memiliki pemahaman yang baik terhadap regulasi dan mekanisme karir dosen sebelum kegiatan. Setelah pendampingan, terjadi peningkatan pemahaman yang ditunjukkan oleh bertambahnya jumlah dosen yang memahami mekanisme kenaikan jabatan fungsional, penilaian kinerja berbasis Tridharma, dan prosedur layanan karir sesuai POS. Selain peningkatan pemahaman sumber daya manusia, kegiatan ini menghasilkan dokumen POS layanan karir dosen yang disepakati dan siap diimplementasikan, serta meningkatkan kesiapan institusional perguruan tinggi mitra dalam menghadapi implementasi kebijakan nasional.